Cesarean Section in Patients with Myomas Located on the Anterior Wall of the Cervix - Hiramatsu, Yuji (The Surgery Journal, 2020)
In patients with uterine myomas undergoing cesarean section, the site of the uterine incision differs depending on the location, size, and number of myomas and the location of the placenta. The difficulty is particularly high when the myomas are located on the anterior wall of the cervix. In all patients, safe fetal birth is the top priority. The incision is usually made to avoid uterine myomas, and enucleation of the myomas is performed after fetal birth. However, in some patients, the fetus must be delivered after enucleating the myomas, so practice is necessary to be prepared for such cases. In this report, I explain the critical points to be noted at the time of cesarean section, especially in patients with myomas located on the anterior wall of the cervix.
Keywords: cesarean section; myoma; myomectomy; incision